2002
DOI: 10.1002/app.11176
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of radiation‐induced acrylamide–acrylic acid hydrogels

Abstract: Acrylamide (AAm)/acrylic acid (AAc) hydrogels in the cylindirical form were prepared by ␥-irradiating binary systems of AAm/AAc with 2.6 -20.0 kGy ␥-rays. The effect of the dose and relative amounts of AAc and pH on the swelling properties, diffusion behavior of water, diffusion coefficients, and network properties of hydrogel systems was investigated. The swelling capacities of AAm/AAc hydrogels were in the range of 1000 -3000%, while poly(acrylamide) (PAAm) hydrogels swelled in the range of 450 -700%. Water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Because of their excellent properties, these SAPs are already well established in various applications, such as disposable diapers, hygienic napkins, cement, drug delivery systems, sensors and agriculture [1]. In such applications high water absorbency or water retention is essential; therefore, [2,3] attempts have been made to improve these absorbent polymers by enhancing their absorbency, gel strength and absorption rate by manipulating the synthesis conditions, such as solvent [4], cross-linking degree [5] and monomer composition. Their use for agriculture-based applications has shown promising results, however in order to reduce cost and effi cacy, very high water absorbency and retention per unit weight of SAPs are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their excellent properties, these SAPs are already well established in various applications, such as disposable diapers, hygienic napkins, cement, drug delivery systems, sensors and agriculture [1]. In such applications high water absorbency or water retention is essential; therefore, [2,3] attempts have been made to improve these absorbent polymers by enhancing their absorbency, gel strength and absorption rate by manipulating the synthesis conditions, such as solvent [4], cross-linking degree [5] and monomer composition. Their use for agriculture-based applications has shown promising results, however in order to reduce cost and effi cacy, very high water absorbency and retention per unit weight of SAPs are essential.…”
Section: Introductionmentioning
confidence: 99%
“…The acetate and nitrate anions of the heavy metal salts affect swelling. Acetate salts dissolve as molecularly in the aqueous solution whereas nitrate salts dissolve as ions 13…”
Section: Resultsmentioning
confidence: 99%
“…In this work, poly( N ‐vinylpyrrolidone‐ co ‐methacrylic acid) P(VP/MAA) copolymer hydrogels were prepared by means of γ‐rays induced homo and copolymerization as a clean and environment friendly source of initiation. The factors effect on the preparation and properties of the hydrogels were investigated and the adsorbing ability of the prepared hydrogels of uranyl ions was examined 9–13…”
Section: Introductionmentioning
confidence: 99%
“…They have acquired a great interest due to the facility of the incorporation of different chelating groups into the polymeric networks. Recently, it has been reported that chelating hydrogels having a specific functional group can be applied to the recovery of precious metal, removal of toxic or radioactive elements from various effluents and to metal preconcentration for environmental sample analysis (13)(14)(15)(16)(17)(18). Such polymeric hydrogels are also promising materials in the field of hydrometallurgical application and water purification, due to their chemical, hydrolytic and thermal stability (19,20).…”
Section: Introductionmentioning
confidence: 98%